2005
DOI: 10.1021/ci050064z
|View full text |Cite
|
Sign up to set email alerts
|

A Virtual Screening Approach for Thymidine Monophosphate Kinase Inhibitors as Antitubercular Agents Based on Docking and Pharmacophore Models

Abstract: Docking and pharmacophore screening tools were used to examine the binding of ligands in the active site of thymidine monophosphate kinase of Mycobacterium tuberculosis. Docking analysis of deoxythymidine monophosphate (dTMP) analogues suggests the role of hydrogen bonding and other weak interactions in enzyme selectivity. Water-mediated hydrogen-bond networks and a halogen-bond interaction seem to stabilize the molecular recognition. A pharmacophore model was developed using 20 dTMP analogues. The pharmacopho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(32 citation statements)
references
References 32 publications
0
32
0
Order By: Relevance
“…Based on a restricted set of 47 inhibitors of TMPKmt modified on the 5-, 2'-, 3'-and 5'-positions of dTMP (described above), the groups of Gopalakrishnan and Desijaru have developed models either to perform virtual screening [39] or 3D-QSAR analysis [40]. Both approaches take advantage of the solved 3D-structure of TMPKmt with dTMP [11].…”
Section: -Computational Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on a restricted set of 47 inhibitors of TMPKmt modified on the 5-, 2'-, 3'-and 5'-positions of dTMP (described above), the groups of Gopalakrishnan and Desijaru have developed models either to perform virtual screening [39] or 3D-QSAR analysis [40]. Both approaches take advantage of the solved 3D-structure of TMPKmt with dTMP [11].…”
Section: -Computational Proceduresmentioning
confidence: 99%
“…After its validation by screening a database of 2,000 molecules containing the training set of 47 molecules, the model was used for the virtual screening of 500,000 compounds. 186 molecules were further selected that could be categorized into five clusters [39].…”
Section: -Computational Proceduresmentioning
confidence: 99%
“…Metrangolo et al presented a review on the great potential of halogen bonds in the design of new and high-value functional materials [14]. Nowadays it has come to light that this specific interaction has utilization in the context of drug design [12][13][14][15][16][17][18]. Auffinger and co-workers screened and assembled a data set of protein and nucleic acid structures to characterize the prevalence and geometry of halogen bonds in biological systems [12].…”
Section: Introductionmentioning
confidence: 99%
“…Also, these molecules can be promising leads to treat tuberculosis by inhibiting DNA synthesis in M. tuberculosis. [4,[9][10][11][12][13][14][15] Several studies were reported for finding the relationship between TMPK Mtub and their inhibitors (usually dTMP) using crystallographic techniques. [4,7,8,16] Considering all available information about TMPK Mtub and its inhibitors, we devised our work in the paradigm of computational chemistry methods.…”
Section: Introductionmentioning
confidence: 99%